Pulmonary arterial hypertension patients display normal kinetics of clot formation using thrombelastography. (1st June 2021) - Lu, Mengyun; Blaine, Kevin P.; Cullinane, Ann; Hall, Courtney; Dulau‐Florea, Alina; Sun, Junfeng; Chenwi, Herman F.; Graninger, Grace M.; Harper, Bonnie; Thompson, Keshia; Krack, Janell; Barnett, Christopher F.; et al.
Abstract : Pulmonary arterial hypertension is characterized by endothelial dysfunction and microthrombi formation. The role of anticoagulation remains controversial, with studies demonstrating inconsistent effects on pulmonary arterial hypertension mortality. Clinical anticoagulation practices are currently heterogeneous, reflecting physician preference. This study uses thrombelastography and hematology markers to evaluate whether clot formation and fibrinolysis are abnormal in pulmonary arterial hypertension patients. Venous blood was collected from healthy volunteers ( n  = 20) and patients with pulmonary arterial hypertension ( n  = 20) on stable medical therapy for thrombelastography analysis. Individual thrombelastography parameters and a calculated coagulation index were used for comparison. In addition, hematologic markers, including fibrinogen, factor VIII activity, von Willebrand factor activity, von Willebrand factor antigen, and alpha2‐antiplasmin, were measured in pulmonary arterial hypertension patients and compared to healthy volunteers. Between group differences were analyzed using t tests and linear mixed models, accounting for repeated measures when applicable. Although the degree of fibrinolysis (LY30) was significantly lower in pulmonary arterial hypertension patients compared to healthy volunteers (0.3% ± 0.6 versus 1.3% ± 1.1, p  = 0.04), all values were within the normal reference range (0–8%). All other thrombelastography parameters were not significantly different between pulmonary arterial hypertension patients and healthy volunteers ( p  ≥ 0.15 for all). Similarly, alpha2‐antiplasmin activity levels were higher in pulmonary arterial hypertension patients compared to healthy volunteers (103.7% ± 13.6 versus 82.6% ± 9.5, p  < 0.0001), but all individual values were within the normal range (75–132%). There were no other significant differences in hematologic markers between pulmonary arterial hypertension patients and healthy volunteers ( p  ≥ 0.07 for all). Sub‐group analysis comparing thrombelastography results in patients treated with or without prostacyclin pathway targeted therapies were also non‐significant. In conclusion, treated pulmonary arterial hypertension patients do not demonstrate abnormal clotting kinetics or fibrinolysis by thrombelastography.